2018
DOI: 10.1016/j.ymben.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Lysine production from the sugar alcohol mannitol: Design of the cell factory Corynebacterium glutamicum SEA-3 through integrated analysis and engineering of metabolic pathway fluxes

Abstract: The amino acid lysine is among the world's most important biotechnological products, and enabling its manufacture from the most attractive new materials is an ever-present challenge. In this study, we describe a cell factory of Corynebacterium glutamicum, which produces lysine from mannitol. A preliminary mutant C. glutamicum SEA-1 obtained by the deletion of the mannitol repressor MtlR in the glucose-based, lysine-producing strain C. glutamicum LYS-12 produced only small amounts of lysine. This limitation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 55 publications
(78 reference statements)
1
43
0
Order By: Relevance
“…As a proof of concept demonstration, base editing was used to remove feedback inhibition of aspartokinase encoded by lysC ( cgl0251 ) by introducing an amino acid transition T311I (C932T or C932T&C933T base editing), which cannot be achieved by our previous MACBETH method (Y. Wang et al, ). This modification was reported to deregulate lysine biosynthesis pathway and cause overproduction of lysine, one of the world's most important biotechnological products (Hoffmann et al, ) (Figure a). nxCas9 3.7(D10A)‐AID was selected for its higher editing efficiency at this genomic locus.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As a proof of concept demonstration, base editing was used to remove feedback inhibition of aspartokinase encoded by lysC ( cgl0251 ) by introducing an amino acid transition T311I (C932T or C932T&C933T base editing), which cannot be achieved by our previous MACBETH method (Y. Wang et al, ). This modification was reported to deregulate lysine biosynthesis pathway and cause overproduction of lysine, one of the world's most important biotechnological products (Hoffmann et al, ) (Figure a). nxCas9 3.7(D10A)‐AID was selected for its higher editing efficiency at this genomic locus.…”
Section: Resultsmentioning
confidence: 97%
“…The average of three biological replicates is plotted. [Color figure can be viewed at wileyonlinelibrary.com] lysine, one of the world's most important biotechnological products (Hoffmann et al, 2018) (Figure 7a). nxCas9 3.7(D10A)-AID was selected for its higher editing efficiency at this genomic locus.…”
Section: Deregulating Feedback Inhibition Of Aspartokinase By Base mentioning
confidence: 99%
“…However, there is no fructokinase (ScrK) in C. glutamicum [36], resulting in that the intracellular fructose should be firstly excreted into extracellular and then reassimilated via fructose-PTS (PTS Fru ). Previous results indicated that hetero-expression of ScrK is beneficial to increase the production of NADPH-dependent products with sucrose or mixed sugar as carbon source [7,[37][38][39]. Therefore, hetero-expression of ScrK from C. acetobutylicum at pfkB gene loci was set as a potential strategy for enhancing l-lysine production on mixed sugar in this study.…”
Section: Hetero-expression Of Scrk Increases L-lysine Production In Cmentioning
confidence: 95%
“…E. coli can naturally assimilate both mannitol and glucose and has been engineered to produce 17.4 g/l of succinic acid from a hydrolyzate made from brown seaweed Saccharina japonica (Bai et al, 2015). Recently, the lysine producing strain C. glutamicum LYS-12 was engineered to assimilate mannitol and efficiently produce 2 g/l L-lysine from this substrate in shake flask experiments (Hoffmann et al, 2018). However, the high salt content of seaweed-based media represents a typical challenge in microbial cultivations and therefore strains with high salt tolerance are required.…”
Section: Introductionmentioning
confidence: 99%